2022
DOI: 10.3390/su142215154
|View full text |Cite
|
Sign up to set email alerts
|

Black Maca (Lepidium meyenii Walp.) Hydroalcoholic Extract as an Ameliorating Agent against Heat Stress Conditions of V-Line Rabbit Does

Abstract: Rabbits are sensitive to heat stress (HS) in hot regions due to difficulty in eliminating excess body heat. We evaluated the ameliorating role of black maca hydroalcoholic extract (BMHE) against HS conditions on the productive and reproductive performance of V-line rabbit does. Rabbits were divided into four equal groups (T1–T4), each containing three replicates. T1 received commercial basal diet (BD) only, whereas T2–T4 received BD and 200, 400, and 600 mg BMHE kg−1 body weight (BW) of doe day−1, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…It is well known that HS is the highest hazard factor deteriorating growing rabbits' growth performance and viability [4,8,[25][26][27][28][29]. Farghly et al [8] reported that rabbits were susceptible to HS, which resulted in deteriorating growth performance indicators in terms of body weight (BW), body weight gain (BWG), feed intake (FI), and feed conversion ratio (FCR).…”
Section: Effect Of Hs On Growth Performancementioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that HS is the highest hazard factor deteriorating growing rabbits' growth performance and viability [4,8,[25][26][27][28][29]. Farghly et al [8] reported that rabbits were susceptible to HS, which resulted in deteriorating growth performance indicators in terms of body weight (BW), body weight gain (BWG), feed intake (FI), and feed conversion ratio (FCR).…”
Section: Effect Of Hs On Growth Performancementioning
confidence: 99%
“…In general, HS negatively impacted reproductive performance in female and male rabbits, which posed a danger to the rabbit business in hot and semi-hot climates [36,37]. Rabbits subjected to HS conditions had a decrease in fertility, embryo development, litter size, litter weight, and milk production [28,37]. Marco-Jimenez et al [37] reported that maternal exposure to high environmental temperatures decreased litter weight, litter size, and kit weight at birth, while the stillborn rate was greater in heat-stressed does during pregnancy.…”
Section: Effect Of Hs On Reproductive Performancementioning
confidence: 99%
See 1 more Smart Citation